Fractional-order evolutionary design of digital circuits - Reis, Cecília (2019)
This paper analyses the performance of a Genetic Algorithm (GA) in the synthesis of digital circuits using a new approach. The novel concept extends the classical fitness function by introducing a fractional-order dynamical evaluation. The dynamic fitness function results from an analogy with control systems where it is possible to benefit the proportional algorithm by including a differential component. For this purpose the non integer derivative is approximated through Pad´e fractions. The experiments reveal superior results when comparing with the classical fitness method.